NOTE ON SOME FURTHER FAINT BLUE VARIABLES - LUYTEN, WJ; HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1956)
We present preliminary information about 6 blue variables discovered in the galactic halo.
BOL OBS TONAN TACUB
Keywords: NOTE, FURTHER, FAINT, BLUE VARIABLES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS